1990
DOI: 10.1007/bf01766489
|View full text |Cite
|
Sign up to set email alerts
|

Different metabolic responses to exercise training programmes in single rat muscle fibres

Abstract: The aim of this report is to elucidate the effects of exercise training on metabolic properties of different muscle fibre types of the rat hindlimb. Single muscle fibres were dissected from soleus (SOL) or extensor digitorum longus (EDL) muscles of Wistar strain male rats trained on a treadmill for 16 weeks. Each fibre was typed histochemically (SO, slow-twitch oxidative; FOG, fast-twitch oxidative glycolytic; FG, fast-twitch glycolytic). Then glycolytic and oxidative enzymes (CK, LDH, PFK, PK, SDH, and MDH) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Additional research on contractile force and speed of contraction in relation to muscle fiber types has been conducted on single fibers [8,9,17,18]. Specifically, it has been previously demonstrated that pressure curve profiles from groups of muscles can be interpreted and related to specific fiber types [10,11,19,20], Thus, the changes in profiles over time in this study may be interpreted similarly to those examined by Laycock and Jerwood [12].…”
Section: Discussionsupporting
confidence: 54%
“…Additional research on contractile force and speed of contraction in relation to muscle fiber types has been conducted on single fibers [8,9,17,18]. Specifically, it has been previously demonstrated that pressure curve profiles from groups of muscles can be interpreted and related to specific fiber types [10,11,19,20], Thus, the changes in profiles over time in this study may be interpreted similarly to those examined by Laycock and Jerwood [12].…”
Section: Discussionsupporting
confidence: 54%
“…It has previously been reported that the optimal training intensity varies among different fiber types and that improvements in oxidative capacity (cytochrome c activity) can be reduced with increases in training intensity (19). Furthermore, previous studies incorporating more moderate-intensity treadmill training in rats have reported significant increases in the CS of the EDL muscle (47,50). Regardless of the explanation, our results suggest that high-intensity interval training can lead to a decrease in the mitochondrial mass of the EDL (a predominantly fast-twitch fiber), as indicated by the significantly lower CS activity in the EDL of trained rats.…”
Section: Adaptations To the Edlmentioning
confidence: 95%
“…With muscle fiber hypertrophy, there is a significant increase in the oxidative enzymes succinate dehydrogenase (SDH) and MDH induced by sprint training and a further increase following endurance training in rat leg muscle [Takekura and Yoshioka, 1990]. This illustrates enzymatic adaptations in the energy-generating machinery of the cell in order to meet the energy needs of increased contractile power.…”
Section: Nadmentioning
confidence: 97%
“…Exercise training has been shown to increase the levels of glycolytic and oxidative enzymes in heart and skeletal muscle [Takekura and Yoshioka, 1990;Stuewe et al, 2000]. With muscle fiber hypertrophy, there is a significant increase in the oxidative enzymes succinate dehydrogenase (SDH) and MDH induced by sprint training and a further increase following endurance training in rat leg muscle [Takekura and Yoshioka, 1990].…”
Section: Nadmentioning
confidence: 99%